Implementasi Metode Simple Additive Weighting (SAW) untuk analisa kepuasan pasien terhadap layanan poli rawat jalan (Studi Kasus: Rumah Sakit Pertamina Bintang Amin) - agung deni (Universitas Teknokrat Indonesia, 2022)
Hospital is a health service institution that provides complete individual health services that provide inpatient, outpatient, and emergency services. One of the hospitals in Lampung province has the motto